2005
DOI: 10.1079/asc41750219
|View full text |Cite
|
Sign up to set email alerts
|

Association of body weight, loinlongissimus dorsiand backfat with body condition score in dry and lactating Holstein dairy cows

Abstract: The lactation cycle of the dairy cow induces large changes in body fat and protein pools, which can be monitored through loin backfat (BF) and longissimus dorsi (LD) measurements. Data from two experiments (exp) using Holstein-Friesian dairy cows (no. = 40 and 32 respectively) were used to study the association of body weight (BW), BF and LD depth with body condition score (BCS) for the last 6 weeks of the dry period (DP) and the fi rst 8 weeks of lactation. Loin and tail BCS were manually assessed (0 to 5 sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
23
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 26 publications
5
23
2
2
Order By: Relevance
“…If the additional free Phe replaced use of peptide-derived Phe in the mammary gland, it is possible that more Met, which liberated energy from milk fat and lactose, provided the energy required to incorporate the peptides back into muscle protein, resulting in some of the increased BCS gain. Jaurena et al (2005) showed that BCS gain reflects accretion of both fat and muscle mass, which was not the case with Phe supplementation alone. This is supported by the tendency for a number of AA (i.e., Met, Lys, Arg, Ala, all branched-chain AA (BCAA)) to decrease in the M/P vs.…”
Section: Discussionmentioning
confidence: 99%
“…If the additional free Phe replaced use of peptide-derived Phe in the mammary gland, it is possible that more Met, which liberated energy from milk fat and lactose, provided the energy required to incorporate the peptides back into muscle protein, resulting in some of the increased BCS gain. Jaurena et al (2005) showed that BCS gain reflects accretion of both fat and muscle mass, which was not the case with Phe supplementation alone. This is supported by the tendency for a number of AA (i.e., Met, Lys, Arg, Ala, all branched-chain AA (BCAA)) to decrease in the M/P vs.…”
Section: Discussionmentioning
confidence: 99%
“…Weight losses in grazing animals are common in rural Sahelian cattle husbandry systems, mainly during the dry season and the transition period from the dry to the rainy season (Ferná ndez-Rivera et al, 2005), and Schlecht et al (1999b) reported body weight losses of up to 22% in nonsupplemented cattle during the dry season. While the situation of urban LI cattle might have been quite similar to the situation of village cattle herds, given their large reliance on feed intake during pasturing, the weight loss of HI cattle especially during the hot dry season remains peculiar and might in part be due to inaccuracies in the conversion of BCSs to LW; this inconsistency might be linked to variations in the magnitude of LW change associated with each unit of BCS change as discussed by Jaurena et al (2005) and Berry et al (2006). Nutrient use efficiency Efficient utilization of resources is an important economic component in livestock production systems whereby the efficiency of feed conversion is greatly influenced by DM intake, digestibility of feeds as well as production performance (Linn et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Since Jaurena et al (2005) showed that BCS gain reflects accretion of fat and muscle mass, the increase in BCS may also be explained by involvement, or activity, of Phe in lipogenesis. Research investigating treatment of type 2 diabetes have shown that use of a Phe-based GPR142 agonist successfully increased serum insulin while decreasing blood glucose concentrations (Du et al, 2012).…”
Section: Discussionmentioning
confidence: 99%